The effectiveness of formative assessment for enhancing reading achievement in K-12 classrooms: A meta-analysis - Xuan, Qianying; Cheung, Alan; Sun, Dan (Frontiers in Psychology, 2022)
This quantitative synthesis included 48 qualified studies with a total sample of 116,051 K-12 students. Aligned with previous meta-analyses, the findings suggested that formative assessment generally had a positive though modest effect (ES = + 0.19) on students’ reading achievement. Meta-regression results revealed that: (a) studies with 250 or less students yielded significantly larger effect size than large sample studies, (b) the effects of formative assessment embedded with differentiated instruction equated to an increase of 0.13 SD in the reading achievement score, (c) integration of teacher and student directed assessment was more effective than assessments initiated by teachers. Our subgroup analysis data indicated that the effect sizes of formative assessment intervention on reading were significantly different between Confucian-heritage culture and Anglophone culture and had divergent effective features. The result cautions against the generalization of formative assessment across different cultures without adaptation. We suggest that effect sizes could be calculated and intervention features be investigated in various cultural settings for practitioners and policymakers to implement tailored formative assessment.